Harnessing immunomagnetic separation and quantum dot-based quantification capacities for the enumeration of absolute levels of biomarker - Park, Hoyoung; Hwang, Mintai P.; Lee, Jong-Wook; Choi, Jonghoon; Lee, Kwan Hyi (IOP PUBLISHING LTD, 2013)
The field of biomarker quantification has experienced a growth parallel to the discovery of new materials. In this paper, we propose an innovative system for the separation and quantification of biomarkers using a simple magnetic bead (MB)-quantum dot (QD) sandwich assay. The basis of the system lies in the interaction between histidine residues on protein G and Ni ions on QDs, and the use of imidazole to selectively detach QDs bound to target biomarkers, in effect enumerating the absolute number of biomarker units. We used C-reactive protein (CRP) as a proof-of-concept and demonstrated a detection sensitivity of 82.5 fmoles in 50 mu 1 of sample volume, a commonly used analytical volume (e.g. ELISA). Although CRP was used as a model to conduct this study, the sensitivity and simplicity of this detachable system make it a viable approach in the quantification of other target analytes.
Keywords: C-REACTIVE PROTEIN; MAGNETIC MICROBEADS; IMMUNOASSAYS; CELLS; HUMIDITY; DISEASE; DESIGN; CANCER